The effects of cyber-ostracism on college students' aggressive behavior: a moderated mediation model - Xing, Jingwen; Kuo, Fengyi (Frontiers in Psychiatry, 2024)
Purpose: This study used questionnaire survey to explore the influence of cyber-ostracism on the aggressive behavior of college students. Specifically, this study explored the mediation role of the basic psychological needs satisfaction, and explored the moderating role of self-integrity. Method: An online questionnaire was designed through a questionnaire website, which was linked and transferred to college students nationwide. 377 valid questionnaires were obtained after excluding invalid questionnaires. Results: Cyber-ostracism had a significant positive predictive effect on the basic psychological needs satisfaction; Basic psychological needs satisfaction play a mediation role between cyber-ostracism and aggression. Self-integrity moderates the association between basic psychological needs and aggression.